Estimativa de geração de biogás no aterro sanitário da bacia leiteira do estado de Alagoas - Costa, Tiago Sandes (2016)
Alternative energy sources are presented as the main inductor of worldwide energy matrix, having biofuels from biomass as its main base. In Brazil, with the oil crisis in the 1970s, pioneering experiments were made in the use of biogas, channeling gas to homes and industries. Recently, with the energy crisis in the country, scholars have resumed research to produce electric power through special turbines that operate by burning gas, turning that energy into electricity. Biogas has in its composition carbon dioxide (CO2) and methane (CH4). Methane - as a fuel - is the main precursor for energy source use. Resulting from organic matter decomposition, the study to be developed aims to assess the feasibility of using biodigesters for the biogas energetic exploitation produced by the decomposition of organic matter found in municipal solid waste, which contains significant amount of biodegradable organic matter that undergo an anaerobic digestion process turning waste into clean energy. The methodological procedure adopted from the perspective of the emission of methane in landfills, if gave from the application of the method of the IPCC. Method this, usually applied to design scenarios of landfills that are not yet operating.Landfill sites are considered one of the most viable alternatives for biogas generation, as they may have techniques for capturing released gases by pickup pipes and its burning. Approved by the State Council of Environmental Protection, the license for sanitary landfill implementation that refers to the Inter-municipal Consortium of Solid Waste Management (ICSWM) - (CIGRES) in the dairy farming, must meet 19 municipalities in the hinterland and the dairy production chain, thus eliminating the dumps in the region. This study aimed to contribute with scenarios forward to the discussions on the need to invest in alternative energy sources that reduce the current stage of greenhouse gases emissions, as well as showing the energy potential that these gases have and the possibility of transforming methane into helpful energy, making biogas a profitable gas, mitigating pollution problems. The landfill has a prospect to generate 5.211.050m3CH4between the reporting period (2015 - 2050) and until 2036, the landfill will generate 2.960.351m3CH4 , starting produce an average 144.751,4m3CH4/year. To design the estimate was used the IPCC model, this method already established in the literature.